2017
DOI: 10.1523/jneurosci.0341-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Opening a New Time Window for Treatment of Stroke by Targeting HDAC2

Abstract: Narrow therapeutic window limits treatments with thrombolysis and neuroprotection for most stroke patients. Widening therapeutic window remains a critical challenge. Understanding the key mechanisms underlying the pathophysiological events in the peri-infarct area where secondary injury coexists with neuroplasticity over days to weeks may offer an opportunity for expanding the therapeutic window. Here we show that ischemia-induced histone deacetylase 2 (HDAC2) upregulation from 5 to 7 d after stroke plays a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 58 publications
(4 reference statements)
3
62
0
Order By: Relevance
“…In the present study, we demonstrated using an MCAO/R model of stroke that HDAC2 deficiency confers significant protection from infarction, supporting the idea that ischemia-induced reduction of Endo-B1 in the penumbra (38) is mediated by HDAC2. Recently, HDAC2 deficiency was reported to be neuroprotective in a photothrombotic model of focal brain ischemia (23). In this model HDAC2 upregulation was observed 5-7 days poststroke and experimental HDAC2 suppression improved stroke outcome only when applied during that time window.…”
Section: The Role Of Hdac2 In Brain Injurymentioning
confidence: 96%
See 1 more Smart Citation
“…In the present study, we demonstrated using an MCAO/R model of stroke that HDAC2 deficiency confers significant protection from infarction, supporting the idea that ischemia-induced reduction of Endo-B1 in the penumbra (38) is mediated by HDAC2. Recently, HDAC2 deficiency was reported to be neuroprotective in a photothrombotic model of focal brain ischemia (23). In this model HDAC2 upregulation was observed 5-7 days poststroke and experimental HDAC2 suppression improved stroke outcome only when applied during that time window.…”
Section: The Role Of Hdac2 In Brain Injurymentioning
confidence: 96%
“…Thus, in AD increased HDAC2 may lead to epigenetic change in gene expression that underlies cognitive impairment. We and others have reported that increased HDAC2 is observed in ischemia/reperfusion injury (4,23) and HDAC2 deficiency is neuroprotective in this setting (23). However, it remains unclear how elevated HDAC2 compromises mitochondrial function, metabolism, and neuronal viability.…”
Section: Introductionmentioning
confidence: 94%
“…As a brief aside, although Kv2.1 has classically been connected with the activation of apoptotic programs (Yu, 2003), other studies have implicated Kv2.1 in oxidant-induced cell death processes not necessarily associated with classic apoptosis (Ito et al, 2017), including toxin-mediated dopaminergic cell death (Redman et al, 2006;Chao et al, 2018), suggesting a wider applicability of our proposed work. Also, cellular K 1 loss may enable neurodegenerative cascades associated with either histone deacetylase (D'Mello, 2009;Lin et al, 2017;Sixto-Lopez et al, 2018) or NLRP3 inflammasome activation (He et al, 2016;Zhou et al, 2016), although Kv2.1 has not yet been directly associated with these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, reduced HDAC4 expression and increased nuclear shuttling are detected in ischemic stroke model cells and animals, while multiple HDACs, including HDAC2, are increased in ischemic stroke models [ 9 11 , 17 , 21 , 64 ]. Moreover, increased HDAC4 expression reduces infarct volume in ischemic stroke model animals and increases cell viability of OGD-treated neurons, while reduced HDAC2 expression promotes neuronal survival and functional recovery in ischemic stroke model animals [ 9 , 10 , 21 , 22 ]. Consistently, pan-HDACs inhibitors and the specific inhibitor of class І HDACs, including HDAC2, alleviate stroke-induced neurological deficits facilitating post-stroke recovery in mice.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…First, dysregulated HDAC4 was observed in ischemic stroke, which does play a key role in the pathogenesis of ischemic stroke and post-stroke recovery by affecting neuronal death, angiogenesis, and neurogenesis [ 16 20 ]. For example, HDAC4 is reduced in ischemic stroke model animals and oxygen-glucose deprivation (OGD)-treated neurons, while increased HDAC4 expression reduces infarct volume in ischemic stroke model animals and increases cell viability of OGD-treated neuronal cells [ 9 , 10 , 21 , 22 ]. In addition, HDAC4 has a significant effect on a cognitive function which could be impaired by ischemic stroke [ 23 ].…”
Section: Introductionmentioning
confidence: 99%